El control interno y la gestión inmobiliaria en la Municipalidad Provincial de Maynas año 2022 - Flores Vasquez, Roxana Julissa (2024)
The different postulates used maintain that internal control is in constant innovation and that is why it leads us to make transcendental and eloquent decisions, unless the decision levels are high hierarchy. The current thesis carries out an investigation to determine the relationship between internal control and real estate management in the Provincial Municipality of Maynas in 2022. With this purpose, this Quantitative, Correlational and design level investigation was carried out. Not Experimental. The research concludes that Internal Control is directly related to Real Estate Management in the Provincial Municipality of Maynas in 2022, demonstrated with the Correlation Coefficient r = 0.316; and the Bilateral Significance = 0.011 obtained in Table No. 13. Likewise, it has been proven that specific hypothesis 1 in internal control is directly related to the risk assessment in real estate management in the Provincial Municipality of Maynas in 2022, having obtained a Correlation Coefficient r = 0.413 and the Bilateral Significance = 0.003 obtained in Table No. 14. On the other hand, in specific hypothesis 2, internal control is directly related to the control activities of movable property in the Municipality Provincial of Maynas year 2022, having obtained a Correlation Coefficient r = 0.703; and the Bilateral Significance = 0.039 obtained in Table No. 15. Finally. Internal Control is directly related to the registration of assets in real estate management of the Provincial Municipality of Maynas in 2022, having obtained a Correlation Coefficient r = 0.167; and the Bilateral Significance = 0.014 obtained in Table No. 16